'I will perpetuate your memory through all generations'1: Institutionalization of collective memory by law in Israel. (1st March 2015) - Tirosh, Noam; Schejter, Amit
If in the past, memory has been understood to be a biological phenomenon relating to the individual and his cognition, today it is clear that memory is a social construction effected by political and cultural processes. This study describes the laws used by the state of Israel in order to form its official memory. It describes how collective memory building is interwoven within the legislation that directs the undertakings of the country's cultural institutions: the educational system, the national symbols, national holidays and memorial days, memory of the Holocaust, preservation of heritage through the erection of museums and physical monuments, commemoration of leaders, and the prevention of certain symbols from entering the public sphere. It demonstrates how the legal apparatus in Israel was mobilized to establish a nationalized collective memory by bridging the 'essential' and 'epochal' elements of nationbuilding and how law can be both a mnemonic practice and an enabler of mnemonic practices. The study of this process provides us with a general lesson on the role of law in collective memory building, with a particular understanding of elements in Israeli nation-building processes.